The Creative systems of the Arabesque and their use in silkscreen and stencil printing - Abdelaziz, Walaa Mohamed (Journal of Humanities & Social Sciences, 2023)
The study aims to reveal the distinctive images of arabesque shapes that have not been processed in an innovative way in the field of hand printing using silk-screen printing methods and stencil methods by addressing kinetic values and different forms of use as an axis to express the unique way of arabesque motifs., The study aims to link printing techniques with the elements of form and content in constructing the piece of art to achieve innovative formulas for a selection of arabesque motifs. The study emphasized the importance of enriching the field of hand-printing with an important decorative element that had not been dealt with in various functions of printing artifacts before, and to clarify the extent of the interrelationship between arabesque motifs and the distinctive techniques of silk screen and stencil styles through the formative capabilities of arabesques that can enrich hand-print designs , The research followed the experimental descriptive approach due to its suitability for this research and the achievement of the objectives. The study reached results, including; The possibility of using the plant arabesque unit as a typographic unit, whether single or within a branched and extended series of motifs, and the possibility of adding a new type of kinetic and innovative values, which is ramification and extension without specific decorative or color pathways, and the formation of an innovative formative relationship between arabesque motifs, silk screen techniques, stencils and other decorative elements like muqarnas , The study recommended encouraging the continuity of research in developing new innovative formulas for arabesque decoration by adopting other printing methods, and conducting more from research and studies on the possibility of enriching the field of textile printing with the dynamic and innovative values of arabesque decorations through computer programs.